INFORMATION PROVISION OF INTEGRATED REPORTING - KARPUSHENKO, M.; LINLIN., TAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Integrated reporting provides a single format for presenting information about the activities of the enterprise - performance indicators of economic, environmental and social activities of the enterprise. Requirements for the quality of both source information and information contained in integrated reporting are growing significantly. The current system of indicators should be determined based on the interests of users of this report, on the one hand, and the tasks of corporate governance - on the other. The issues of information support of integrated reporting as well as the materiality of its indicators are considered in the work. The whole information array is grouped into five blocks - information of regulatory and legal nature; information of normative-reference character; information contained in the accounting system; information contained in financial and statistical reports characterizing the property and financial condition of the enterprise; non-system data. The article solves such tasks as the analysis of the information base of integrated reporting, determining the features of its compilation, the basic principles of reporting in accordance with the international standard of integrated reporting. The obtained results - the system of information support of integrated reporting is defined. Conclusions: further development of integrated reporting should be aimed at such important aspects as methods of obtaining information, generalization of various management systems (management accounting, monitoring, analysis of financial stability) in the process of preparing internal integrated reporting.